CHALLENGES AND STRATEGIES IN TEACHING ENGLISH TO NON-ENGLISH MAJORS IN BUSINESS AND ACCOUNTING PROGRAMS - Dewi Muliasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study investigates the challenges and strategies in teaching English to non-English majors, specifically within business and accounting programs at Institut Teknologi Bisnis AAS Indonesia. Using a qualitative case study approach, the research explores the perspectives of both instructors and students to identify key difficulties and effective practices. The study reveals that student motivation is a significant challenge, with many students perceiving English as peripheral to their main field of study. To address this issue, instructors have integrated business-related content into the English curriculum, enhancing relevance and engagement. Additionally, the research highlights the diversity in student proficiency levels, which necessitates the use of differentiated instruction and peer-assisted learning to cater to varying needs. The integration of technology and blended learning approaches has been beneficial but also presents challenges related to access and instructor proficiency. Institutional support for resources, collaboration between language and subject-matter experts, and continuous professional development are crucial for overcoming these challenges. The findings offer insights into improving English language education for non-English majors and provide recommendations for educators and institutions. Keywords: English language teaching, non-English majors, business and accounting programs, blended learning